TRANSFORMASI DIGITAL PENDIDIKAN MADRASAH: PERAN STRATEGIS EMIS DALAM TATA KELOLA BERBASIS DATA - Sukma Ayundah Lestari; Ahmad Fauzi; Ali Mustafa (Jurnal Manajemen Pendidikan, 2025)
In the digital era 4.0, the transformation of public management in the Islamic education sector faces challenges such as the lack of student data integration, inefficient manual reporting, and gaps between central policies and regional implementation, which hinder transparency, accountability, and data-based decision-making under the Ministry of Religious Affairs. This study analyzes the role of the Education Management Information System (EMIS) as a strategic instrument to realize data-based governance in 707 madrasahs (mostly private) in Sidoarjo Regency, as well as to identify obstacles to its implementation. Using a descriptive-exploratory qualitative approach, this research involves purposive sampling of informants such as EMIS operators and madrasah principals. Primary data was collected through semi-structured interviews, participant observation, and documentation, while secondary data came from a review of relevant literature. Findings show that EMIS has successfully integrated key data on institutions, students, teachers, and infrastructure via a dashboard and structured data collection process, supporting the planning of BOS assistance and the development of madrasahs efficiently and in real-time. However, significant obstacles include limited digital infrastructure, low human resource capacity among operators, and weak regulatory coordination, resulting in data validity gaps.